Hubungan Pemberian Metilprednisolon dan Tocilizumab pada Pasien Covid-19 di Rumah Sakit Al Islam Bandung - Zetananda Kirana Fauziyah Dakirun; Heni Muflihah; Endang Suherlan (UNISBA Press, 2022)
Abstract. Corona Virus Disease (COVID-19) is a pandemic that has spread to Indonesia. West Java is the province with the second-highest number of COVID-19 cases. Immunomodulators are recommended in COVID-19 patients, with inconsistent benefits across studies. Methylprednisolone acts non-specifically, while tocilizumab acts specifically at the IL-6 receptor. One indication of the administration of immunomodulators is the severity of COVID-19. This study was conducted to determine the relationship between administration of methylprednisolone and tocilizumab with the severity in hospitalized COVID-19 patients at Al Islam Hospital Bandung (RSAI). This study is an analytic observational with cross-sectional approach and uses medical records. The subjects of this study were confirmed COVID-19 patients who were hospitalized at Al Islam Hospital Bandung span from December 2020 until June 2021. The medical records were analyzed including oxygen saturation (SpO2) and administration of methylprednisolone or tocilizumab during hospitalization. Total research subjects are 116 people, consist of 31 people (59,61%) received methylprednisolone and 35 people (54,68%) received tocilizumab. There were 50 people (43,1%) had severe COVID-19 (SpO2 < 90%) and 66 people (56,9%) had non-severe COVID-19 (SpO2 90%). There was no relationship between the administration of methylprednisolone or tocilizumab with the severity of COVID-19 (p = 0,766). No relationship found between the selection of immunomodulators, methylprednisolone or tocilizumab with severity of COVID-19. Further research is needed to examine clinical conditions other than oxygen saturation to determine the severity COVID-19 disease in order to evaluate more accurately indications for immunomodulatory therapy. Abstrak. Corona Virus Disease (COVID-19) merupakan pandemi yang menyebar ke Indonesia. Jawa Barat adalah Provinsi dengan kasus COVID-19 kedua terbanyak. Imunomodulator direkomendasikan pada pasien COVID-19, dengan manfaat yang tidak konsisten di berbagai hasil penelitian. Metilprednisolon bekerja secara non-spesifik, sedangkan tocilizumab bekerja secara spesifik pada reseptor IL-6. Salah satu indikasi pemberian imunomodulator adalah derajat penyakit COVID-19. Penelitian ini dilakukan untuk mengetahui hubungan pemberian metilprednisolon dan tocilizumab dengan derajat penyakit pada pasien COVID-19 rawat inap di Rumah Sakit Al Islam Bandung (RSAI). Penelitian ini berupa observasional analitik dengan pendekatan cross sectional dan menggunakan data rekam medis. Subjek penelitian ini adalah pasien terkonfirmasi COVID-19 yang dirawat inap di RSAI pada periode Desember 2020 – Juni 2021. Data rekam medik yang dianalisis meliputi saturasi oksigen (SpO2) dan pemberian metilprednisolon atau tocilizumab selama dirawat. Total subyek penelitian berjumlah 116 orang. Jumlah ini terdiri dari 31 orang (59,61%) mendapat metilprednisolon dan 35 orang (54,68%) mendapat tocilizumab. Terdapat 50 orang (43,1%) memiliki derajat berat (SpO2 < 90%) dan 66 orang (56,9%) derajat tidak berat (SpO2 ≥ 90%). Tidak terdapat hubungan antara pemberian metilprednisolon atau tocilizumab dengan derajat penyakit (p = 0,766). Tidak terdapat hubungan pemilihan imunomodulator, metilprednisolon atau tocilizumab dengan derajat penyakit COVID-19. Penelitian lanjutan perlu menkaji kondisi klinis selain saturasi oksigen untuk penentuan derajat penyakit COVID-19 agar lebih tepat mengevaluasi indikasi terapi imunomodulator.